Efficacy and safety of vitamin D in tuberculosis patients: a systematic review and meta-analysis. Issue 7 (3rd July 2022) - Goyal, Jagdish Prasad; Singh, Surjit; Bishnoi, Ramakishan; Bhardwaj, Pankaj; Kaur, Rimple Jeet; Dhingra, Sameer; Yadav, Dharmveer; Dutta, Siddhartha; Charan, Jaykaran
ABSTRACT: Background: Evidence from the basic research and epidemiological studies indicates a beneficial effect of vitamin D in the treatment of tuberculosis (TB). However, the evidence from randomized controlled trials (RCTs) is inconsistent. Objectives: This systematic review and meta-analysis was performed to synthesize evidence regarding role of vitamin D versus placebo for the management of TB. Materials and Methods: We searched PubMed and Cochrane Clinical Trial Registry for RCTs comparing vitamin D versus placebo for the treatment of TB. RCTs enrolling adult patients with TB receiving vitamin D in addition to standard treatment were included. Data were pooled using random effects model. The study was conducted according to PRISMA guidelines and protocol was registered with PROSPERO (CRD42016052841). Results: Of 605 identified references, 12 RCTs were included. The overall risk of bias in included studies was low or unclear. There was no significant difference between vitamin D and placebo group for any outcomes of efficacy (time to culture conversion, time to smear conversion, rate of culture conversion, and rate of smear conversion) or safety (mortality, serious adverse events, and nonserious adverse events) Conclusion: Vitamin D administered with standard treatment has no beneficial effect in the TB patients as compared to the placebo.